2019
DOI: 10.3390/nu11081728
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of a Virgin Olive Oil Enriched with Bioactive Compounds in Spontaneously Hypertensive Rats

Abstract: Olive oil and its derivatives have been described to exert beneficial effects on hypertensive states and cardiovascular disease prevention. We studied the effects of chronic consumption of extra virgin olive oil (EVOO), enriched in bioactive compounds from olive fruit and leaves, on blood pressure, endothelial function, oxidative and inflammatory status, and circulating cholesterol levels, in spontaneously hypertensive rats (SHR). Thirty SHR were randomly assigned to three groups: a control untreated SHR group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 42 publications
3
26
1
2
Order By: Relevance
“…It is plausible that the anti-hypertensive effect shown by Gs was due to more than one component or to an additive effect of polyphenols and glycoalkaloids, which need to be administered for a long period of time. The effects of Gs could be more pronounced if treatment is started before the onset of hypertension and continued at length, as indicated in a recent paper on the anti-hypertensive effect of an enriched olive oil, that produced a reduction in blood pressure after five weeks of treatment and reduced cardiac hypertrophy after eight weeks of treatment [4,28]. A similar observation was also reported by other authors [29].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It is plausible that the anti-hypertensive effect shown by Gs was due to more than one component or to an additive effect of polyphenols and glycoalkaloids, which need to be administered for a long period of time. The effects of Gs could be more pronounced if treatment is started before the onset of hypertension and continued at length, as indicated in a recent paper on the anti-hypertensive effect of an enriched olive oil, that produced a reduction in blood pressure after five weeks of treatment and reduced cardiac hypertrophy after eight weeks of treatment [4,28]. A similar observation was also reported by other authors [29].…”
Section: Discussionsupporting
confidence: 61%
“…Four weeks of Gs treatment may not be enough to restore all cardiovascular parameters, especially those linked to morphological modifications. In fact, the literature suggests that treatments with natural compounds inducing morphological modifications have to be continued for longer periods [28]. Our results show that none of the treatments affected plasma glucose and triglycerides, which in our study were not significantly different in WKYs and SHRs.…”
Section: Discussioncontrasting
confidence: 59%
“…Therefore, it is desirable to increase the polyphenol content of VOO in order to improve its benefits. In this way, previous studies have demonstrated the cardioprotective effect of VOO enriched in bioactive compounds from the olive oil in animals [8] and humans [9,10]. In fact, recent studies have shown a strong ergogenic effect on physical activity and remodeling of more efficient mitochondrial super-complexes with lower reactive oxygen-derived species production at doses 20 mg/kg and 300 mg/kg [11,12].…”
Section: Introductionmentioning
confidence: 93%
“…In line with this hypothesis, in the same SHR model, the administration of EVOO [75], pomace oil [76], or related antioxidant polyphenolic components (oleuropein, hydroxytyrosol) was shown to lower BP significantly. Investigated mechanisms range across anti-oxidative activities [75,77], changes of aminopeptidase activities favoring the production of Ang 2-10 (in this way compensating the activity of Ang II) and the clearance of Ang III and Ang IV [75], increase in the endothelial nitric oxide synthase (eNOS) expression [76,78], and reduction of plasma Ang II [75] (Figure 4). Correspondingly, our previous research has shown that OO polyphenols and related human serum metabolites, as found in human serum upon EVOO ingestion, can decrease the endothelial activity and expression of NADPH oxidase, as shown by the reduced levels of intracellular ROS and decreased expression and activity of MMP-2 and MMP-9 in endothelial cells [79,80] and adipocytes [81,82].…”
Section: Olive Oil Anti-hypertensive Effects: Mechanistic Evidence Frmentioning
confidence: 99%